Pengaruh Penggunaan Media YouTube Terhadap Hasil Belajar Matematika Siswa Kelas IV Gugus III Kota Bengkulu - Fatimah, Siti; Agusdianita, Neza; Tarmizi, Pebrian (Universitas Bengkulu, 2025)
The aim of this research is to find out how the use of YouTube videos affects the mathematics learning outcomes of grade IV students in Bengkulu City. This research uses a matched only pretest-posttest control group design and is quantitative with a quasi-experimental methodology. Class IV of SDN 3 Kota Bengkulu was the research population. The sample selection used total sampling, meaning that all members of class IV SDN 3 Bengkulu City were in class IVA as the experimental class and class IVB as the control class. The pretest and posttest are descriptive questions. Prerequisite tests, hypothesis tests, and descriptive statistics are data analysis methods in this research. Apply t-test to evaluate the hypothesis. At a significance level of 5%, the research findings produce Sig.(2-tailed) = 0.000 < 0.005. Specifically, students in the experimental class got the highest pretest score of 60, while students in the control class got the lowest score of 20 with an average of 43.12. In the experimental class, the highest pretest score was 61 and the lowest score was 8. The homogeneity test results were in the homogeneous version, and the normality test results showed that both samples had a normal distribution. Apart from that, there is a difference in the average score of the experimental class (83.64) and the control class (64.28) on the posttest of 22.36. Thus, it can be said that the use of YouTube media for grade IV students in Bengkulu City has an impact on their mathematics learning outcomes.